Designer's guide to Eurocode 1 : actions on bridges : EN 1991-2, EN 1991-1-1, -1-3 to -1-7 and EN 1990 annex A2 - Calgaro, J. A. (Jean-Armand).; Tschumi, M. (Marcel).; Gulvanessian, H. (London : Thomas Telford, 2010)
The design process of a bridge includes several steps. One of the major steps is the determination of actions & combinations of actions. These actions are imposed loads due to traffic, climatic actions, actions due to water or soil subsidence, construction loads & accidental actions.
'Eurocodes Expert ... a new ICE and Thomas Telford initiative set up to assist in creating a greater awareness of the impact and implementation of the Eurocodes within the UK construction industry' - t.p. verso.
Includes bibliographical references and index.
Keywords: Bridges -- Design and construction -- Standards -- Europe; EN1991 Eurocode 1 (Standard).